Wilms' tumor in a 51-year-old patient: An extremely rare case and review of the literature - HU, JIA (Mol Clin Oncol, 2016)
Wilms tumor or nephroblastoma is a common kidney malignant tumor in childhood, accounting for ~5% of all pediatric tumors. At present, reports on Wilms' tumor occurring in adults, particularly at ages >30 years, are extremely rare. The majority of the cases of adult Wilms' tumor are closely associated with chemotherapy. Furthermore, in rare cases, Wilms' tumor is characterized by three classic types of cells, namely blastemal, stromal and epithelial cells. We herein report a case of Wilms' tumor with three classic types of cells on histological examination in a 51 year-old male patient who had received prior chemotherapy. The patient promptly underwent radical nephrectomy and remains alive. A review of previously presented cases of adult Wilms' tumor from PubMed database was also performed.